SYSTEM AND METHOD FOR OPTIMIZING A CRUISE VERTICAL PROFILE SUBJECT TO A TIME-OF-ARRIVAL CONSTRAINT - DE PRINS, Johan L; GARRIDO-LOPEZ, David; YOCHUM, Thomas E; SCHARL, Julien; FIGLAR, Bastian (2024)
A system and a method for planning and flying a cost-optimal cruise vertical profile in combination with a required time-of-arrival (RTA) constraint. The method may be implemented as a single function in a flight management system (FMS). The FMS (10) plans the aircraft trajectory with cruise vertical and speed profiles that are optimized to minimize flight cost (e.g., fuel burn) while meeting the time constraint. When appropriate under the circumstances, this integrated function is also able to degrade the cruise vertical profile in order to open the window of achievable RTAs and increase the RTA success rate. The method also monitors progress of the flight along the planned trajectory as actual flight conditions may differ from the forecasted flight conditions, and readapts the cruise speed profile when the estimated arrival time is deviating from the RTA constraint by more than a specified threshold.